Valuation of intellectual capital in the service sector of Mexican companies listed on the Mexican Stock Exchange (Bolsa Mexicana de Valores) BMV 2014-2019. (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2023)
Today, knowledge is the primary source in creating and generating competitive advantage and wealth in companies. Managing intellectual capital is synonymous with running a competitive business and is employed in building the knowledge management model. Therefore, this article identifies the positive impact that intellectual capital and its components, measured through VAICTM, have on financial performance variables such as Return on Assets (ROA), Return on Equity (ROE), and Employee Productivity (TLP) in service sector companies listed on the Mexican Stock Exchange during the period 2014-2019. Data analysis allows us to observe that specifically, human capital and employed capital are the indicators that influence financial performance, and the intellectual capital indicator measured through VAICTM also positively impacts the financial results of organizations.
Keywords: human capital; services; intellectual capital; structural capital and capital employed